Evaluating the Use of Daily Care Notes Software for Older People with Dementia. Issue 7 (21st April 2019) - Maiden, Neil; Pitts, Kristine; Pudney, Kevin; Zachos, Konstantinos
ABSTRACT: There has been little research to investigate the impact of software to support the care for older people with dementia care. This article reports the evaluation of software adapted to support one key person-centered task for the care of older residents with dementia – recording and sharing daily care notes. The evaluation on the dementia wing of 1 residential home for over 6 months revealed that use of the software on mobile devices carried by the carers increased the number and volume of daily care notes recorded, but only for the types of content that were already being recorded by carers. Carers reported more advantages that resulted from daily care notes once in digital form than from the documenting task, as well as barriers to the use of mobile digital software to record daily care notes.